O conceito “Allélon” como princípio de alteridade na teologia trinitária de Bruno Forte - Santos, Merlise dos (2023)
The present dissertation proposes to reflect the concept “Allélon” as a principle of otherness in Bruno Forte's Trinitarian theology. For the theologian, the other is today a concern of the postmodern subject's thinking. The elimination of the other no longer causes indignation, on the contrary, in the name of neoconservative ideologies or forms, inhuman practices of intolerance and violation of the right of the other are legitimized. The acceptance of otherness and the love for one another are the pathways of meaning for non-violent forms of recognition of the other. For the author, love presupposes a dynamic of relationships, an 'I' that gives and a 'you' that receives. The same logic of love that demands that the Trinity be at the same time plurality, otherness, reciprocity, a gift. It is not without consistency that Forte speaks of a Trinitarian ethos, which for him is the recovery of the category of revelation, the foundation of the Hebrew-Christian faith, the history of salvation woven from intimately united events and words. On the other hand, recovery of the unity between dogma and ethics that founds the need to deepen the relationship between the Trinitarian faith and the ethos that underlies our social behavior. The concept “Allélon” used by Forte with a strong biblical connotation appeals to a semantic sense that hermeneutically refers man to his mission as a collaborator of God in the history of salvation